COMPUTATIONAL IMPACT PRESSURE OF THE FLOATPLANE’S BOTTOM IN VARIOUS OF DEADRISE AND FLARE ANGLES - Sulisetyono, Aries; A. Washoya, Zambilly; Zubaydi, Achmad (Journal of Applied Engineering Science, 2022)
The water impact at the bottom of a floatplane during landing is one of the main issues related to the structure strength. The free fall of the floater to the water surface is suitable modelling to obtain a pressure value against the optimal design angle of the deadrise and flare. The computational fluid dynamics (CFD) technique under the dynamic mesh feature in FLUENT is applied to compute the impact pressure due to free-falling of the 2D cross-section of the floater in four variation deadrise angles. The simulation results stated that the angle of deadrise affects the pressure on the floater bottom area whose it decreases along with the increase in deadrise angle. The presence of flares also contributes to lowering the pressure value under all deadrise angle conditions. Comparison of simulation results with Wagner’s formula shows a good agreement for all models with an average error of about 5.27%.